EXPERIMENTAL STUDY OF POLLUTION AND SIMULATION ON INSULATORS USING COMSOL® UNDER AC VOLTAGE - BENGUESMIA, Hani (Université de M'sila, 2019)
The flashover of pollution, observed on the insulators used in high voltage transmission, is one of the most important power transmission stakes. It is a very complex problem due to several factors including the modelling difficulties of complex shapes of insulators, different pollution densities at different regions, non-homogeneous pollution distribution on the insulator surface and unknown effect of humidity on the pollution. In the literature, some static and dynamic models have been developed by making some assumptions and omissions to predict the flashover voltages of polluted insulators. This paper aims to experimentally analyse the flashover process and simulation of the distributions of the potential and the electric field under 50 Hz applied voltage on a real model simulating the 175CTV outdoor insulators largely used by the Algerian Company of Electricity and Gas (SONELGAZ). This real model is studied under non-polluted (distilled water), and polluted (distilled water and sand) environments. The simulations were carried out by using the COMSOL multiphysics software. This program uses the finite element method to solve the partial differential equations that describe the field. Experimental results made in the laboratory and simulation results are original and found to be congruent.
Keywords: insulator; flashover; pollution; high voltage; potential; electric field